ANALYSIS OF STUDENT ERRORS IN SOLVING STORY PROBLEMS BASED ON KASTOLAN'S THEORY - Astri Zulaika Pohan; Andi Susanto; Christina Khaidir (UIN Imam Bonjol Padang, 2025)
Errors in solving math story problems remain a common problem among students. This is due to the lack of in-depth analysis by teachers of the types of errors made by students based on Kastolan's theory, resulting in the same patterns of errors being repeated. Based on this problem, this study aims to identify and describe the types of errors made by students in solving mathematical story problems based on Kastolan's theory. This study uses a quantitative descriptive approach with a sample of 36 students in class X.E6 at SMAN 2 Bukittinggi, selected through purposive sampling. The research instrument was a story problem test on trigonometry consisting of five questions. The data were analyzed using descriptive statistics to obtain the percentage of each type of error. The results showed that 21 students (59.44%) made conceptual errors, 24 students (67.67%) made procedural errors, and 22 students (62.78%) made technical errors. Thus, procedural errors were the most dominant type of error made by students. These findings indicate the need for more systematic learning strategies and an emphasis on procedural understanding in solving mathematical story problems.